Coaching to Bedside Shift Report and Its Correlation to Hospital Consumer Assessment of Healthcare Providers and Systems and Value-Based Purchasing Dimension Scores: A Multihospital Implementation Study. (January 2023) - O'Donnell, Lauren; George, Elisabeth; Donnelly, James; Bilderback, Andrew; Buchanan, Dan
Abstract : OBJECTIVE: The objective of this multihospital study was to investigate how the intervention of coaching to bedside shift report (BSR) correlates with Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) outcomes and relates to Centers for Medicare and Medicaid Services (CMS) Hospital Value-Based Purchasing (VBP) Program points over a 4-year period (2017-2020) for an acute care hospital health system. BACKGROUND: Hospital leaders' responsibilities include intertwined areas of patient experience and fiscal accountability. Coaching to BSR is reported to have numerous benefits to the patient's experience. Published studies completed with hospital systems evaluating the intervention of coaching to BSR and how it correlated to patient experience and VBP are limited. METHODS: Coaching to BSR was implemented at 16 adult acute care hospitals. Patient-reported BSR rates were collected in tandem with HCAHPS for 4 years. Statistical correlations were assessed between patient-reported BSR and HCAHPS and consequential effect on VBP dimension scores. RESULTS: Coaching to BSR had a significant impact on top- and bottom-box "rate the hospital" HCAHPS scores at a system and hospital level. Value-based purchasing points and percentages increased over 2017-2020, potentially leading to lower CMS penalty claims over the period the BSR was implemented. CONCLUSIONS: Coaching is a key factor when creating a favorable patient experience. The implementation and sustainability of coaching to BSR may result in improved patient experience ratings and increase VBP point accumulation to hospital systems.